Dhat Syndrome: Delay in Seeking Psychiatric Help, Cultural Myths and Co-Morbid Depression - Shakeel M Ansari; Shakila Mulla (Medsci Publications, 2017)
Introduction: Dhat syndrome is widely reported in India. Existing myths exaggerate this problem. Hence current study was conducted to assess role of myths in the course of dhat syndrome. Delay in seeking psychiatric help was also assessed and its association with co-morbid depression was analysed. Material and method: Analytical cross-sectional study was carried out on 100 dhat syndrome cases visiting Psychiatry OPD in a tertiary care centre. Study tools included Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition, Hamilton Depression Rating Scale and Questionnaire regarding 'myths and misconceptions about sex'. Results: The mean age of Dhat syndrome cases was 23.35 years. Mean observed delay in seeking psychiatric help was 8.06 months. 98% had previous consultations prior visiting a psychiatrist. Significant delay was observed in cases who previously visited quacks or Indigenous medical practitioners. These previous consultations reinforced various myths among cases. Prevalence of depression in dhat syndrome was 43%. Delay in seeking psychiatric help was significantly associated with depression. Conclusion: Non-psychiatric consultations escalate myths related to dhat syndrome and contribute to delay in seeking psychiatric help. This delay needs to be curtailed by community awareness, as it worsens the outcome in the form of co-morbid depression.